Classification of tree species based on their accumulation and exclusion of heavy metals, and the influence of heavy metals on species abundance on Copperbelt tailings dams in Zambia - Chirwa, Paxie W. (University of Pretoria, 2024)
Dissertation (MSc (Forest Management and Environment))--University of Pretoria, 2019.